2021
DOI: 10.1039/d0ob01884h
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in using 4DPAIPN in photocatalytic transformations

Abstract: 1,3-Dicyano-2,4,5,6-tetrakis(diphenylamino)-benzene (4DPAIPN) is a typical donor–acceptor fluorophore, with diphenylamino as an electron donor and dicyanobenzene as an electron acceptor. It has emerged as a powerful and an attractive metal-free organophotocatalyst...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(37 citation statements)
references
References 91 publications
0
37
0
Order By: Relevance
“…Given that cathodic reduction of 4‐CzIPN resulted in a meaningful improvement in photochemical deamination yield, we examined other isophthalonitrile catalysts. This investigation revealed that 4‐DPAIPN [82] promotes the reduction of model substrate 1 in nearly quantitative yield under electrophotocatalytic conditions. Overall, the structural diversity of the potent photocatalysts identified through these studies suggest that reductively induced photoactivity is a general phenomenon and provides a clear link between catalyst structure and reaction outcome.…”
Section: Resultsmentioning
confidence: 78%
“…Given that cathodic reduction of 4‐CzIPN resulted in a meaningful improvement in photochemical deamination yield, we examined other isophthalonitrile catalysts. This investigation revealed that 4‐DPAIPN [82] promotes the reduction of model substrate 1 in nearly quantitative yield under electrophotocatalytic conditions. Overall, the structural diversity of the potent photocatalysts identified through these studies suggest that reductively induced photoactivity is a general phenomenon and provides a clear link between catalyst structure and reaction outcome.…”
Section: Resultsmentioning
confidence: 78%
“…Given that cathodic reduction of 4-CzIPN resulted in a meaningful improvement in photochemical deamination yield, we examined other isothphalonitrile catalysts. This investigation revealed that 4-DPAIPN [74] promotes the reduction of model substrate 1 in nearly quantitative yield under electrophotocatalytic conditions.…”
mentioning
confidence: 79%
“…We next evaluated whether 4-DPAIPN was promoting this reaction via excitation of its radical anion congener. Under electrochemical stimulation 4-DPAIPN acts as a far more potent photoreductant than anticipated by its established redox potentials (E1/2 PC + /PC * ) = -1.3 V and E1/2 (PC/PC -) = -1.5 V vs SCE) [74] (Figure 2). First, we conducted a series of control experiments and found that catalyst, electrolysis, and light were all required for product formation.…”
mentioning
confidence: 92%
“…For example, the reduction of 6 would be predicted to be endothermic by nearly 2 V (>40 kcal/mol at room temperature) based on the most reducing conventional redox couple of 4-DPAIPN (E1/2(PC/PC •-) = -1.5 V vs SCE). 77 We next subjected radical clock 9 to this formate-driven system to validate the intermediacy of an aryl radical. As anticipated, these conditions furnished the five-membered ring product in high selectivity for radical cyclization.…”
Section: A B Cmentioning
confidence: 99%